An economic mathematical model for the import of coal to Ukraine - Stohniy B.S.; Kaplin M.I.; Bilan T.R. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
With the advent of new technologies in the metallurgy and the thermal power industry, the demand for coal of coking marks, most of which are not produced in Ukraine or have low consumption characteristics, is greatly increased. This raises the problem of the provision of Ukraine’s economy with coal products of the required quality in the given volume, which can be solved only through their purchases abroad.We propose an economic mathematical model of the income of imported coal to Ukraine with regard for the price indicators of the transport and opportunities of Ukraine’s transport infrastructure. The network model is based on the concept of production activity by Kantorovich and belongs to the class of models of the production type. Estimations for the coal income by means of railway and sea transportation facilities from near and remote countries such as the USA, South African Republic, Australia, and Kazakhstan are done. The conditions of the economic profitability of the coal import from foreign countries, as an alternative to that from the Russian Federation, are discussed.